Tsunami wave propagation by voronoi diagram - Yuvaraj, V; Rajasekaran, S; Nagarajan, D (International Journal of Engineering and Technology, 2018)
Cellular automata is the model applied in very complicated situations and complex problems. It involves the Introduction of voronoi diagram in tsunami wave propagation with the help of a fast-marching method to find the spread of the tsunami waves in the coastal regions. In this study we have modelled and predicted the tsunami wave propagation using the finite difference method. This analytical method gives the horizontal and vertical layers of the wave run up and enables the calculation of reaching time.Â Â